Role of income and skill development in plastic waste-to-wealth entrepreneurship: Empowering women in Sub-Saharan Africa - Muktar, Itai Monday; Bassey, Enwongo Imeh; Timilehin, Olubiyi Olasoji (Asian Economic and Financial Review, 2025)
Addressing plastic waste pollution has become a global environmental concern. Although plastic pollution harms terrestrial and aquatic ecosystems, it also presents opportunities for wealth creation. This study investigates the role of plastic waste-to-wealth entrepreneurship in enhancing women’s empowerment through income generation and skill development in Lagos State, Nigeria. Using a quantitative research design with a Structural Equation Modelling (SEM) approach, data were collected from 302 women plastic waste pickers across three major dump sites in Lagos State, the largest consumer market in Africa. The study achieved a response rate of 98%. Findings reveal a significant positive relationship between plastic waste-to-wealth initiatives and women’s income, as well as a strong link between skill development and empowerment among women entrepreneurs. The study recommends increased financial support, access to resources, and strategic partnerships with plastic waste cooperatives to help women expand their businesses and income. It further emphasises the importance of training and skill acquisition programs in strengthening empowerment and promoting sustainable entrepreneurship.